Revitalisasi Sistem Ekonomi Syariah terhadap Perkembangan Ekonomi Syariah - Anisa Suci; Efri Islami Hasibuan (STIKes Ibnu Sina Ajibarang, 2025)
The Islamic economic system discusses the various challenges faced by Indonesia in developing this sector, the potential of the nation, and the achievements that have been achieved to date. The writing of this scientific paper aims to identify the main challenges in the development of the Islamic economy in Indonesia, explore strategic potentials that can be utilized, and examine the extent to which the development of the Islamic economy has taken place in the country. The data sources used come from literature such as relevant books, as well as additional information from online searches to enrich insights. The method used is a qualitative descriptive approach, which describes the situation systematically based on available data. The results of the analysis show that despite a number of obstacles, such as limited human resources, low Islamic financial literacy, and infrastructure challenges, the implementation of the Islamic economic system still has strong prospects. This is supported by the great potential that Indonesia has, including a very large Muslim population, government support, and increasing public interest in sharia-based products and services.